ANALISA KEKUATAN IMPAK DAN DAYA SERAP AIR BIOKOMPOSIT SERAT KULIT JAGUNG - BIOPLASTIK SARI PATI KENTANG DENGAN VARIASI MASSA SERAT - Delaputra, Okaldo; Kencanawati, Cok Istri Putri Kusuma; Winaya, I Nyoman Suprapta (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
7Abstract7 The level of plastic waste pollution has been getting higher so it is necessary to find solutions to this problem, one of which is by developing bioplastic materials. Bioplastics are plastics that can be used like plastic in general, but are easily biodegradable. The use of bioplastics added with natural fibers can improve the characteristics of the material. This study was conducted to determine the impact strength and water absorption of corn husk fibers biocomposites with a ratio of potato starch essence matrix with corn husk fiber, which is 99%: 1%; 97% : 3%; and 95%: 5% compliant with ASTM D6110 for impact strength and ASTM D570-98 for water absorption. The results of the impact test with a fibers mass of 3% showed the most optimal impact strength of 0.01285 J/mm2. This is because the fibers are well distributed and evenly distributed on the matrix, this causes the matrix and fibers bonds to be stronger and able to absorb greater energy, which means the ability to receive higher impact strength. Testing the water absorption of corn husk fibers biocomposites is hydrofolic or water-loving properties, evidenced by the high ability to absorb water reaching values above 80%. Keywords : Biocomposite, Corn Husk Fibers, Potato Starch Extract, Impact Strength, Water Absorption, fibers mass variation, Bioplastic